Faktor-faktor Yang Mempengaruhi Kemampulabaan Bank - Edy Safni Rosa; Kellin Noventia (Jurnal Ilmiah Manajemen Kesatuan, 2023)
This study aims to determine whether the Effect of Third Party Funds, Loan To Deposit Ratio and Credit Interest Rates in this study partially and simultaneously affect profitability as measured by Return On Assets (ROA). The population in this study were book IV banking companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period as many as 7 companies, then the sample was determined using the Purposive Sampling method, namely the sample was selected from a population of certain criteria, either expertly or scientifically. The analytical method used is the classical assumption test, multiple linear regression analysis test, partial test of determination coefficient test (t test), and simultaneous test (f test). Data testing was carried out using IBM SPSS Statistics 25 Software. The results of this study indicate that: 1) Third Party Funds (X1) have a significant effect on Profitability (ROA), because the more funds collected by the public in the form of savings, demand deposits, deposits, the more banks will distribute interest costs on the product so that it can reduce the income or profitability of a Bank. 2) Loan to Deposit Ratio (X2) has a significant effect on Profitability (ROA), because the more loans that are disbursed, the higher the interest income that will be obtained by the bank with the assumption that if the loans disbursed are in a smooth state, it will increase the bank's profit. the. 3) Credit Interest Rates (X3) have a significant effect on Profitability (ROA) because the more people who make credit, the credit interest income will increase so that it will increase the profitability of a Bank. 4) Third Party Funds, Loan to Deposit Ratio and Interest Rates Credit has a simultaneous and significant effect on Profitability (ROA). Keywords: Third Party Funds, Loan To Deposit Ratio, Credit Interest Rates, Profitability